Meta‐analysis: the impact of disease activity at conception on disease activity during pregnancy in patients with inflammatory bowel disease. Issue 5 (15th July 2013) - Abhyankar, A.; Ham, M.; Moss, A. C.
Summary Background The rate of exacerbation of inflammatory bowel disease (IBD) during pregnancy varies in the published literature. Aim We sought to perform a systematic review and meta‐analysis of the effects of disease activity at conception on disease course during pregnancy in women with IBD. Methods Published studies and abstracts from standard sources were screened for appropriate studies. Data were pooled and analysed using funnel and forest plots. Quality assessment scores were given using GRADE criteria. Results Fourteen studies were eligible for inclusion; ten studies contained patients with UC (N = 1130), and six studies contained patients with CD (N = 590). In patients with UC there was a significantly higher risk ratio of active disease during pregnancy in patients who commenced pregnancy with active disease (55%), when compared with those in remission at conception (36%) (RR 2.0, 95% CI: 1.5–3, P < 0.001). This risk was also higher in patients with CD (RR 2.0, 95% CI: 1.2–3.4, P = 0.006). Thirteen of the studies rated 'low' in all domains of a quality assessment, and there was significant statistical heterogeneity. Conclusions Patients with IBD who conceive when their disease is active are more likely to have active disease during pregnancy than those who conceive when in remission. All studies used in this analysis had a high risk of bias therefore further studies are required.